Population growth highlights and trends, Queensland ... : [Web site] - Queensland. Department of Infrastructure and Planning; Queensland. Department of Local Government, Planning, Sport and Recreation. Planning Information and Forecasting Unit. (Brisbane : Dept. of Local Government, Planning, Sport and Recreation, 2004)
This serial, archived from the Departmental Web site, contains analyses of population estimates for Queensland, its regions (Statistical Divisions) and Local Government Areas (LGAs)
2009 issue is prepared by the Dept. of Infrastructure and Planning.
Produced by the Planning Information and Forecasting Unit.
Title from title screen (viewed on July 27, 2005)
Electronic data.
Also available in printed format.
Mode of access: World Wide Web
Keywords: Housing -- Queensland -- Statistics -- Periodicals; Queensland -- Population -- Statistics -- Periodicals